Feasibility of extracting specimens from the site of preventive ileostomy and its impact on stoma retraction of laparoscopic low anterior resection for rectal cancer - Bai Junge; Wang Zhexue; Yang Ming; Ma Xiaolong; Liu Zheng; Chen Haipeng (结直肠肛门外科)
[Objectives] To investigate the feasibility of extracting specimens from the preventive ileostomy site during laparoscopic low anterior resection for rectal cancer and its impact on ileostomy closure. [Methods] A retrospective analysis was conducted on the clinical data of 223 patients who underwent laparoscopic low anterior resection of rectal cancer combined with preventive ileostomy in Cancer Hospital of Peking Union Medical College, Chinese Academy of Medical Sciences from September 2015 to September 2019. Patients were divided into two groups based on whether specimens were extracted from the preventive ileostomy site: the ileostomy site extraction group (n＝114) and the non-ileostomy site extraction group (n＝109). The surgical indicators, wound and stoma-related complications, stoma closure surgery-related indicators, and stoma closure interval time were analyzed. [Results] Compared with the non-ileostomy site extraction group, the ileostomy site extraction group had a shorter operation time[169.0 (136.0，207.8) min vs. 211 (179，250) min，Z＝-5.755，P<0.001] and less intraoperative blood loss [30 (20，50) mL vs.50 (50，100) mL，Z＝-5.382，P<0.001]. In the non-ileostomy site extraction group, 4 patients (3.7%) with postoperative abdominal auxiliary incision bleeding, 2 patients (1.8%) with incision infection, and 1 patient (0.9%) with incisional hernia. In the ileostomy site extraction group, there were no abdominal auxiliary incisions or incision-related complications. The total incidence of incision-related complications was significantly different between the two groups (χ2＝7.558，P＝0.006). In the non-ileostomy site extraction group, 40 patients (36.7%) developed stoma-related complications, including 8 patients with stoma parastomal hernia (7.3%), 1 patient with prolapse (0.9%), 1 patient with ostomy retraction (0.9%), 1 patient with stricture (0.9%), 3 patients with bleeding (2.8%), and 1 patient with granuloma (0.9%), 17 patients with stoma peristomal dermatitis (15.6%), 4 patients with true skin ulceration (3.7%), and 4 with superficial mucocutaneous separation (3.7%). In the ileostomy site extraction group, 31 patients (27.2%) developed stoma-related complications, including 5 patients with stoma parastomal hernia (4.4%), 1 patient with stoma retraction (0.9%), 1 patient with bleeding (0.9%), 21 patients with stoma peristomal dermatitis (18.4%), and 3 patients with true skin ulceration (2.6%). There was no significant difference in the total incidence of stoma-related complications between the two groups (χ2＝2.319，P＝0.128). In the non-ileostomy site extraction group, 102 patients (93.6%) underwent ileostomy closure surgery, while in the ileostomy site extraction group, 102 patients (89.5%) underwent ileostomy closure surgery. There was no significant difference in the ileostomy closure rate between the two groups (χ2＝1.204，P＝0.272). Compared with the non-ileostomy site extraction group, the interval time of the ileostomy site extraction group from surgery to ileostomy closure was shorter [217 (147.5，289.5) min vs. 256.5 (193.8，371.0) min, Z＝-3.595, P<0.001], the surgical time was shorter [（80.8±25.3）min vs. （95.7±30.4）min，t＝14.902，P<0.001], and the intraoperative blood loss was less [20(10，20) mL vs. 30(20，50) mL，Z＝-4.927，P<0.001]. Optimal scale regression analysis showed that the site of specimen collection (P＝0.014), neoadjuvant chemotherapy (P＝0.037), adjuvant chemotherapy (P＝0.044), and postoperative complications (P＝0.018) were independent factors affecting the interval time of ileostomy closure. [Conclusion] Preventive ileostomy for specimens extracted during laparoscopic low anterior resection can shorten surgical time and interval time from surgery to ileostomy closure, reduce intraoperative blood loss and incision-related complications without increasing stoma-related complications, proving to be safe and feasible. In addition, the site of specimen collection, neoadjuvant chemotherapy, adjuvant chemotherapy, and postoperative complications are independent factors affecting the interval time from surgery to ileostomy closure.